2022
DOI: 10.1186/s13046-022-02456-5
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr viral product-containing exosomes promote fibrosis and nasopharyngeal carcinoma progression through activation of YAP1/FAPα signaling in fibroblasts

Abstract: Background The progression of nasopharyngeal carcinoma (NPC) is profoundly affected by Epstein-Barr virus (EBV) infection. However, the role of EBV in the intercommunication between NPC and surrounding stromal cells has yet to be explored. Methods NPC biopsies were obtained for immunohistochemical (IHC) analyses. Clinical correlations between the expression of active YAP1/FAPα and the fibrotic response and between YAP1/FAPα and the density of cytot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 46 publications
0
19
0
Order By: Relevance
“…Consistent with the "seed and soil" theory of metastasis proposed by Paget in 1889 (78), the best predictors of the success of ecological dispersal are those variables that whether cancer cells have enough ecological adaptive and reproductive ability (79)(80)(81). In the primary sites, for example, NPC cells can secrete matrix metalloproteinases that physically alter their environments (82)(83)(84), contribute to angiogenesis via vascular endothelial growth factor (VEGF) production (85-87), manipulate the content and functions of extracellular vesicles (EVs) (88)(89)(90)(91)(92) or change tight vascular capillary endothelial walls by inducing endothelial-mesenchymal transition (EnMT) (93) of the organ ecosystem. This is well reflected in the detection of magnetic resonance imaging (MRI) with extensive local infiltration of adjacent soft tissues, erosion of skull base, etc.…”
Section: Npc As Invasive Species and Its Metastasis As An Ecological ...mentioning
confidence: 99%
“…Consistent with the "seed and soil" theory of metastasis proposed by Paget in 1889 (78), the best predictors of the success of ecological dispersal are those variables that whether cancer cells have enough ecological adaptive and reproductive ability (79)(80)(81). In the primary sites, for example, NPC cells can secrete matrix metalloproteinases that physically alter their environments (82)(83)(84), contribute to angiogenesis via vascular endothelial growth factor (VEGF) production (85-87), manipulate the content and functions of extracellular vesicles (EVs) (88)(89)(90)(91)(92) or change tight vascular capillary endothelial walls by inducing endothelial-mesenchymal transition (EnMT) (93) of the organ ecosystem. This is well reflected in the detection of magnetic resonance imaging (MRI) with extensive local infiltration of adjacent soft tissues, erosion of skull base, etc.…”
Section: Npc As Invasive Species and Its Metastasis As An Ecological ...mentioning
confidence: 99%
“… [ 173 ] TGF-β Mesothelioma Colorectal cancer Prostate cancer Bladder cancer Triger the myofibroblast differen-tiation [ 30 ] FAP and EBV-encoded latent membrane protein 1 (LMP1) Nasopharyngeal carcinoma Generate CAFs via enhancing YAP1 signalling and increasing FAP expression. [ 177 ] COL6A1 Osteosarcoma COL6A1-positive EVs generate CAFs expressing interleukins, α-SMA, and TGF-β [ 81 ] Gain-of-function p53 Ovarian cancer Instigate CAF phenotypes in fibroblasts through the Nrf2-dependent pathway [ 39 ] Annexin A1 Pancreatic cancer Induce myofibroblasts features in the fibroblasts and endothelial cells [ 82 ] Lin28B Pancreatic cancer Generate CAFs from pancreatic stellate cells through activating let-7/HMGA2/PDGFRβ axis. [ 83 ] Hyal1 Prostate cancer Stimulate fibroblast chemotaxis by the increased adhesion and activating FAK signalling.…”
Section: Cancer-derived Evs Can Dictate Preferable Caf Characteristic...mentioning
confidence: 99%
“…The replication and the mitotic isolation of EBV episomes, as well as the safeguarding of EBV genomes in inert contaminated cells, all rely upon EBNA1. Additionally, it is demonstrated that EBNA1 upholds cell endurance after DNA harm by instigating genomic insecurity and initiating a few cell qualities through transcriptional enactment [ 74 , 75 ].…”
Section: Latent Gene Products Of Ebvmentioning
confidence: 99%
“…The EBV genome’s EBNA2-encoding (BamHI-WYH) region allows for strain diversity, allowing all viral isolates to be divided into type 1 (EBV-1, B95.8-like) and type 2 categories (EBV-2, Jijoye-like). Due to this chromosomal variance, the EBNA2 protein may exist in two antigenically different versions that only share 50% amino acid similarity [ 74 ].…”
Section: Latent Gene Products Of Ebvmentioning
confidence: 99%
See 1 more Smart Citation